2021
DOI: 10.1002/acr.24393
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Specimen Length and Number of Sections and Diagnostic Yield of Temporal Artery Biopsy for Giant Cell Arteritis

Abstract: Objective To investigate the association between specimen length and number of sections evaluated and the diagnostic yield of temporal artery biopsy (TAB) for giant cell arteritis (GCA). Methods A pathologist reviewed all TABs performed for suspected GCA between January 1991 and December 2012. The blocks of all the inadequate and negative biopsy specimens were recut, and further slides at deeper levels were stained with hematoxylin and eosin in order to avoid missing inflammatory changes. Results In total, fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…2. Length of specimen: With non-continuous pathology, the lesion cannot be localized a longer biopsy specimens and bilateral sites are recommended [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…2. Length of specimen: With non-continuous pathology, the lesion cannot be localized a longer biopsy specimens and bilateral sites are recommended [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Muratore et al proposed recently that TABs with post-fixation lengths of at least 5 mm may be sufficient to diagnose GCA (52). The fresh biopsy should be at least 10% longer to allow for shrinking.…”
Section: Temporal Artery Biopsymentioning
confidence: 99%
“…The fresh biopsy should be at least 10% longer to allow for shrinking. The same study advised evaluating at least three further sections at deeper levels to not miss inflammatory changes if the initial result is negative (52).…”
Section: Temporal Artery Biopsymentioning
confidence: 99%
“… 26 However, a recent study by Muratore et al found that a postfixation temporal artery biopsy specimen length of at least 5 mm, corresponding to a prefixation surgical specimen length of 7–10 mm, maximizes the diagnostic accuracy of temporal artery biopsy. 27 They also reported that, in order not to miss inflammation limited to adventitial and/or periadventitial small vessels as described above, at least three other sections at deeper levels should be evaluated in all uninflamed temporal artery biopsy specimens. 27 The TABUL study by Luqmani et al compared ultrasound to temporal artery biopsy in the diagnostic approach of GCA.…”
Section: Temporal Artery Biopsymentioning
confidence: 99%
“… 27 They also reported that, in order not to miss inflammation limited to adventitial and/or periadventitial small vessels as described above, at least three other sections at deeper levels should be evaluated in all uninflamed temporal artery biopsy specimens. 27 The TABUL study by Luqmani et al compared ultrasound to temporal artery biopsy in the diagnostic approach of GCA. 28 The authors reported a lower sensitivity of the temporal artery biopsy compared to that of the ultrasound (39% vs 54%).…”
Section: Temporal Artery Biopsymentioning
confidence: 99%